Low predictive value of positive transplant perfusion fluid cultures for diagnosing postoperative infections in kidney and kidney–pancreas transplantation. Issue 12 (22nd August 2012) - Cotter, Meaghan P; Smyth, Elizabeth; O'Gorman, Joanne; Browne, Sarah; Hickey, David P; Humphreys, Hilary
Abstract : Aims: Infection following transplantation is a cause of morbidity and mortality. Perfusion fluid (PF) used to preserve organs between recovery and transplantation represents a medium suitable for the growth of microbes. We evaluated the relevance of positive growth from PF sampled before the implantation of kidney or kidney–pancreas (KP) allografts. Methods: Between January 2007 and January 2011, 548 kidney/KP transplants were performed in our centre. A retrospective review of patient records with culture-positive PF was performed. Results: PF was received from 483 (88%) patients, of which 35 (7%, 95% CI 5.3% to 9.9%) were positive for bacteria (31/483, 6.4%, 95% CI 4.6% to 9.8%) and fungi (4/483, 0.8%, 95% CI 0.3% to 2.1%). Thirty-two of the 35 culture-positive PF (91.4%, 95% CI 77.6% to 97%) were considered insignificant. The remaining three patients developed sepsis postoperatively, which was considered to be possibly related to growth in PF; Escherichia coli in one and Klebsiella pneumoniae in two. Of the non-skin flora bacteria cultured from PF, six were resistant to the prophylactic antibiotic given intraoperatively, but only one developed infection postoperatively ( E coli, resistant to the co-amoxiclav). Conclusions: Significant attributable morbidity associated with PF-positive culture results was relatively rare. Culture of organisms other than Enterobacteriaceae or fungi are likely to represent contamination.